Pengaruh Sarana Dan Prasarana Terhadap Motivasi Siswa Belajar Seni Budaya (Seni Musik) - Firman Hidayat; Ardipal Ardipal (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
This study aims to determine and describe how the influence of facilities and infrastructure on student motivation in learning cultural arts in class X MAN 2 Padang Panjang. This type of research is quantitative research using descriptive methods. Data collection techniques are carried out through questionnaires, as well as documentation. Data management techniques are editing, coding, scoring, tabulating data. Data analysis techniques are instrument tests and prerequisite tests. The results showed that there was an influence of school facilities and infrastructure on the learning motivation of grade X MAN 2 Padang Panjang students, X Koto District, Tanah Datar Regency. It was found that the influence of Facilities and Infrastructure on Motivation (Y) obtained the value of the coefficient of determination written R Square of 0.392 can be explained that the proportion of influence of Facilities and Infrastructure is 41.5% while the remaining 39.2% is influenced by other factors from outside the variables used in this study.